KEPEMIMPINAN PEREMPUAN DALAM ISLAM PERSPEKTIF MUHAMMADIYAH DAN HIZBUT TAHRIR INDONESIA - Aminah, Aminah (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Women's issues are always interesting to study, because it is closely related to issues or gender roles. There are two sides of views on the role, which one considers that women only deserve to occupy the role of domestic, the other view assumes that women have the same rights as men, including acting in the territory, including the head of state. Regarding gender, the Muhammadiyah and the Hizb ut-Tahrir Indonesia also get respond. Both religious social organizations are very different in voicing his views. Based on the story of the queen of Saba located on an Naml letter, and some letters in the al-Qur'ân which explains the equality between men and women, Muhammadiyah confirms the permissibility of women became heads of state. Muhammadiyah also critizied hadith of Abu Bakr who demonstrated unpermissibility of female leading. According to the hadith Muhammadiyah has seen in contextual interpretation, so the hadith can not be generalized. Unlike Muhammadiyah, Hizb ut-Tahrir Indonesia (HTI) actually makes the narratives of Abu Bakr as the basis for banning women became heads of state. Based on the principle of al-'ibrah bi umu>mi al-lafz}i La> bi khus}u>s as-saba>b, HTI drew the conclusion that the hadith is a general ban is based on general pronunciation is not particularly cause. Therefore, not only for the keharamannya Persian princess, but also to all women.